The effects between currency appreciation and stock market in China and Japan applied time series econometric techniques. - Cheng, Shen (2008)
The present study applies the time series econometric techniques of cointegration and Granger causal to analyze the natural causal relationship between stock market and foreign exchange rate for both China and Japan and uses the EGRACH model to examine the asymmetric effects within stock markets. The very similar empirical results from testing the daily data of China (during the period from 2001 to 2008) and Japan (during the period from 1985 to 2000) proved the existence of long term negative relationship, bilateral causality between stock price and foreign exchange rate and asymmetric effects within the stock market by taking into account the effects from foreign exchange market. Based on my findings above, the paper tried to theoretically summarize some major lessons could be drawn from the experience of yenÃÂ¢ÃÂÃÂs appreciation in macroeconomic perspective. After assessing the Chinese monetary policies in terms of the mentioned lessons, some advises are given in order to further adjust monetary polities in a correctly way.